Between politics and preaching: the Tunisian al-Nahda movement in the city of Sousse, 1973-2014 - McCarthy, R (2016)
Research on Islamist movements in the Middle East and North Africa has tended to focus on leaders and ideologues to explain transformation over time. This thesis, however, is a political ethnography of the Tunisian al-Nahda movement that focuses on one city to present a fine-grained micro-study of the shifting trajectories of an Islamist organisation. The main original finding is that the relationship between politics and preaching in the practice of Islamism can be conflicting and irreconcilable, rather than cohesive and interdependent. By privileging the experiences of non-elite activists, this thesis also identifies informal networks, an individual reimagining of the Islamist project, and peripheral activism as explaining resilience under repression. It argues that al-Nahda has undergone strategic and intellectual adaptations, which have incurred costs, culminating in a decision in 2016 to separate the political party from social, religious, and cultural work. This thesis is based on fourteen months of fieldwork among current and former al-Nahda activists in the city of Sousse. It addresses the origins of the movement in Sousse to ask why the movement first emerged in the city and what mechanisms of mobilisation were deployed. It rethinks the politicisation of the movement in the 1980s to challenge previous assumptions that suggested the movement grew away from its preaching origins. The thesis addresses the effect of two decades of repression, excavating the prison experience and the period of social exclusion which followed and which disaggregated the movement into its constituent parts. It explains why the movement fragmented after 2011 even as activists rebuilt and redefined their project. In conclusion, the thesis accounts for the tension between politics and preaching within the movement, interrogates the party-movement separation of 2016, and asks what lessons similar Islamist experiences in the region might offer al-Nahda.